Structures Congress 2013 2013
DOI: 10.1061/9780784412848.231
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Stability Response of Columns in Multi-Tiered Braced Steel Frames for Industrial Applications

Abstract: This paper presents a study on the seismic response of multi-tiered braced steel frames. The seismic demand and stability of the columns in a 4-tiered special X-braced frame structure located in a high seismic area and designed according to current AISC seismic provisions is evaluated. The drift demand in the individual bracing tiers and the combined column axial force and in-plane flexural demand are evaluated through nonlinear time history analysis. Detailed finite element analysis of one column under demand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Column is torsionally fixed at the tier level to simulate the torsional restraint provided by the strut. Additional detail is given in Imanpour et al (2013). The results of the analysis showed that flexural buckling takes place at a time t = 9 s, after brace tension yielding has developed in Tier 2 but before it occurred in Tier 1.…”
Section: Finite Element Analysis Of An Isolated Columnmentioning
confidence: 97%
See 2 more Smart Citations
“…Column is torsionally fixed at the tier level to simulate the torsional restraint provided by the strut. Additional detail is given in Imanpour et al (2013). The results of the analysis showed that flexural buckling takes place at a time t = 9 s, after brace tension yielding has developed in Tier 2 but before it occurred in Tier 1.…”
Section: Finite Element Analysis Of An Isolated Columnmentioning
confidence: 97%
“…The analysis can therefore be used to assess the nonlinear seismic response of the frame example, including the expected force demand on the columns and tier drift response, such that the proposed design requirements can be validated. Detail of the modeling and analysis assumptions are given in Imanpour et al (2012aImanpour et al ( , 2013. Nonlinear incremental static (pushover) analysis of the frame is performed to determine member forces and tier drifts as the frame deforms up to the anticipated story deflection.…”
Section: Nonlinear Static (Push-over) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies on the seismic behavior of MTCBFs demonstrated that frames designed according to contemporary seismic provisions are susceptible to inelastic drift concentration within a single tier (Imanpour et al 2012a(Imanpour et al , 2012b(Imanpour et al , 2013Imanpour and Tremblay 2012). Concentration of inelastic drift within a single tier may result in brace fracture due to ultra low cycle fatigue (Roufegarinejad andTremblay 2012, Fell et al 2009), or weak-axis flexural yielding of the columns (Imanpour et al 2012a(Imanpour et al , 2012b(Imanpour et al , 2013Imanpour and Tremblay 2012;Stoakes and Fahnestock 2012b). In addition to compromising in-plane stability of the columns, previous research found that weak-axis flexural yielding may also lead to out-of-plane and/or torsional column instability (Imanpour et al 2012b;Stoakes and Fahnestock 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, existing studies on the seismic behavior of MTCBFs have not fully accounted for column axial forces, or torsional loading and deformation of the columns in MTCBFs. In the studies by Imanpour et al (2012aImanpour et al ( , 2012bImanpour et al ( , 2013 and Imanpour and Tremblay (2012), torsion-induced shear stresses acting on the columns were not considered to interact with normal stresses due to axial and flexural demands. In the study by Stoakes and Fahnestock (2012b), the axial force was assumed uniform over the height of the columns.…”
Section: Introductionmentioning
confidence: 99%